Case Report: Early Breast Cancer Recurrence Mimicking BIA-ALCL in a Patient With Multiple Breast Procedures - Materazzo, Marco; Vanni, Gianluca; Pellicciaro, Marco; Anemona, Lucia; Servadei, Francesca; Giacobbi, Erika; Farinaccio, Andrea; Pistolese, Chiara Adriana; Perretta, Tommaso; Chiocchi, Marcello; Bruno, Valentina; Tacconi, Federico; et al. (Frontiers in Surgery, 2021)
Breast reconstruction plays a fundamental role in the therapeutic process of breast cancer treatment and breast implants represent the leading breast reconstruction strategy. Breast Implant Associated-Anaplastic Large Cell Lymphoma (BIA-ALCL), locoregional recurrence in the skin flap, and skin flap necrosis are well-known complications following mastectomy and immediate breast reconstruction (IBR). We report a case of locoregional cancer recurrence in the mastectomy flap mimicking BIA-ALCL, in a patient who underwent 6 breast procedures in 4 facilities across 15 years including immediate breast reconstruction with macrotextured breast implants. Despite the rate and onset of the disease, clinicians should be aware of BIA-ALCL. Due to the risk of false-negative results of fine-needle aspiration, clinical suspicion of BIA-ALCL should drive clinicians’ choices, aside from cytological results. In the present case, surgical capsulectomy of the abnormal periprosthesic tissue revealed a locoregional recurrence.